PECULIARITIES OF USING FOLK MUSIC SAMPLES OF OUR ANCESTORS IN THE EDUCATION OF YOUNG PEOPLE - Nurdinov Qamardin Patidinovich (Journals Park Publishing, 2022)
The article deals with the role of folk music in the education of the younger generation, the study of spiritual heritage in conjunction with universal values, a wide range of conditions for high artistic talent and thinking. In order to create as much as possible their intellectual potential, it is planned to increase the level of education in harmony with the music.
Keywords: folk music; education; national music